Early evidence of the development of primary care networks in England: a rapid evaluation study - Judith Smith; Sarah Parkinson; Amelia Harshfield; Manbinder Sidhu (NIHR Journals Library, 2022)
Background: Primary care networks are groups of general practices brought together in July 2019 to hold shared budgets and develop new services in response to NHS England (now NHS England and Improvement) policy. This study examined the early implementation of primary care networks, especially what has helped or hindered progress, how they operate in relation to pre-existing collaborations and issues for rural networks. Objective: To produce early evidence about the development of primary care networks to inform policy for their future development. Our research questions were to investigate (1) the contextual background of primary care networks; (2) the rationale for general practices to enter into collaborations; (3) the early learning from establishing primary care networks; (4) barriers to and facilitators of effective collaboration across general practices; and (5) the likely future progress of primary care networks in the English NHS, including in the light of COVID-19. Design: A qualitative cross-comparative case study evaluation comprised four work packages: (1) a rapid evidence assessment; (2) a workshop with academics, policy experts and patient/public representatives; (3) interviews with stakeholders, observations of meetings, a survey and documentary analysis across four case study sites; and (4) analysis and synthesis of findings to develop recommendations for the next stage of the development of primary care networks. Results: Primary care networks have been implemented in a timely manner and have established a range of new local health services. Previous general practice collaborations provide much-needed support in terms of management, leadership and infrastructure, although they can be a source of tension within networks where interests, goals and ways of working do not align. Reasons for collaborative working typically focus on the sustainability of primary care and a desire for better-integrated services, although those cited as the basis for joining primary care networks were mostly related to policy and financial incentives. Early evidence reveals operational success in establishing organisational structures, recruiting to new roles and providing services as required by the national specification. Effective management and leadership, particularly with respect to having a committed clinical director, and constructive relationships between primary care networks and clinical commissioning groups, are important in ensuring success. In rural areas there was some perceived lack of fit with aspects of the primary care network specification, alongside existing challenges of providing primary care to rural populations. Limitations: Arranging and carrying out interviews proved difficult given the workload associated with implementing networks and wider time pressures. Following the onset of the COVID-19 pandemic, the team was unable to undertake planned face-to-face workshops to explore findings. Given that primary care networks were in their first year of operation at the time of this evaluation, we were cautious in drawing definitive conclusions. Conclusions: Key lessons focus on increasing the engagement of general practices and wider primary care teams with networks; building leadership and management capacity to support networks in fulfilling their contractual obligations and meeting local health needs; and clarifying how primary care networks will operate in the post-COVID-19 health and social care system. Future work: Future work could involve evaluating the impact and effectiveness of primary care networks using quantitative and qualitative measures; undertaking research in both rural and urban areas, exploring the extent to which this context is significant; examining the cost and effectiveness of sustaining and extending leadership and management support within primary care networks; and understanding the relationships between primary care networks and the wider health and care system. Study registration: This study is registered as PROSPERO CRD42018110790. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care and Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 27. See the NIHR Journals Library website for further project information.